THE INFLUENCE OF FAMILY EXPECTATIONS AND THE PHENOMENON OF GUILT ON THE FORMATION OF RESPONSIBLE QUALITIES IN STUDENTS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the influence of the family environment and parents’ subjective expectations on the development of responsibility among students. The study analyzes psychological aspects of parental expectations that contribute to the formation of healthy responsibility, as well as those that generate destructive feelings of guilt. Particular attention is paid to the relationship between personal autonomy, locus of control, and students’ emotional well-being. The article presents scientifically grounded conclusions and practical recommendations aimed at strengthening internal motivation and supporting students’ psychological development.
Keywords: responsibility, guilt, family expectations, locus of control, personal autonomy, students